Bede on Jude - Moore, Nicholas J. 1984- (2025)
The Venerable Bede is known today as the first English historian. Yet he considered himself to be an exegete above all else, and was received as such in the medieval church. Among his various works of biblical interpretation is the first extant Latin commentary on the Catholic Epistles. Dating from the early stage of Bede’s writing, the commentary is generally characterized as concerned with the plain or literal sense of the text. This article offers a reading of the final book of Bede’s commentary, on the Epistle of Jude. Here we find evidence of Bede’s learning and his interest in a range of canonical and doctrinal questions. Significantly, the article demonstrates that Bede also develops early and brief figural readings of the text, and thus disproves the contention that he is concerned only with its literal sense.
Keywords: Christology; canon of Scripture; figural exegesis; Catholic Epistles; Epistle of; Jude; Bede the Venerable